Dynamic myocardial response to exercise in children with transposition of the great arteries post arterial switch operation. (4th February 2022) - Henry, M; Grotenhuis, H; Slorach, C; Fan, S; Grosse-Wortmann, L; Mertens, L; Cifra, B
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The arterial switch operation (ASO) has improved outcomes for patients with transposition of the great arteries (TGA) however the long-term impact on myocardial function and functional reserve during exercise remains poorly described. The aim of this study was to evaluate left (LV), and right ventricular (RV) myocardial response to exercise in children post ASO using semi-supine cycle ergometry stress echocardiography (SSCE). Methods: This is a single-center cross-sectional study. Participants prospectively underwent exercise stress echocardiography using a semi-supine bicycle and a stepwise exercise protocol. Systolic (s') and diastolic (e') tissue Doppler velocities, as well as myocardial acceleration during isovolumic contraction (IVA) were measured at rest and during exercise at incremental heart rates (HR) in the basal segments of the RV lateral wall, IVS and LV lateral wall. Systolic and diastolic reserve were evaluated by plotting s' and e' against HR while contractile reserve was assessed by plotting IVA values against HR which represents the force-frequency relationship (FFR). Results: A total of 40 patients with TGA and 29 controls were included. There were no differences between groups in age (14.6 ± 2.9 vs 14.3 ± 3.1 years, p= 0.75), sex (male= 30/40 vs 20/29 p= 0.58), and resting HR (67 ± 12 vs. 71 ± 12 bpm, p = 0.31). Peak HR was lower in the ASO group (142.2 ±12.4 vs 157 ± 12.3 bpm, p< 0.01). At rest, the ASO group showed lower s' in the RV and IVS (RV s': 5.7 ± 1.4 vs. 10.2 ± 2.1 cm/s, p <0.001; IVS s': 4.2 ± 1.3 vs. 6.2 ± 1.8 cm/s, p< 0.001); lower IVA in the IVS and LV (IVS: 1.01 ± 0.37 vs. 1.23 ± 0.4 m/s2, p= 0.03; LV: 0.86 ± 0.32 vs. 1.1 ± 0.4 m/s2, p =0.02), and reduced e' in all segments. At peak exercise the ASO group showed reduced s', e', and IVA in all segments (table1). When plotted against HR, there was blunting of the s' slope in RV and septal segments while the LV s' slope was similar between groups. There were no differences in e' slope when compared to controls (figure 1). The ASO group showed a blunted IVA response to HR in all measured segments compared to controls. Conclusion(s): Our data demonstrate patients post ASO have reduced RV and LV contractile reserve in response to exercise. The etiology and long-term implications of these abnormalities however remains to be described.